Asmare : revendo valores e forjando uma nova gestão em contexto de crise - Ângela Rosane de Oliveira (2017)
This study sought to study the revitalization process of Asmare, an association of waste pickers of recyclable materials in Belo Horizonte, Minas Gerais in a context of crisis. The study sheds light on Asmare’s history, its management style, particularly that which concerns its impact on society, the association’s organization and the workers that belong to it. Field study was based on qualitative research carried with waste pickers in Asmare’s two warehouses and the process was divided into three stages: documentation; observations and interviews; and organization and analysis of data. The study maintained a permanent dialogue with authors who have studied waste pickers, in addition to valuing the participation of the association members in group discussions with regard to issues that were emerging in the research and the findings. This was a way to foster members’ critical outlook on the dilemmas and strategies they were facing. The study revealed controversial issues, such as: the participation of external technical staff in the association’s management and the recent appropriation of this management process by the association members, and Asmare’s identity, values and norms as a self-managed association. Considering that this study took place during the same period the municipal government withdrew its financial support from Asmare, the findings show that waste pickers have produced specific knowledge with regard to their daily work and despite the crisis, the association continues to fully operate without overlooking its conflicts and making decision according to its acquired values. While the rupture with the municipality’s agreement was a catalyst in Asmare’s crisis, it also served to encourage the group to create new possibilities and establish its own management style.